Recent Updates on Development of Drug Molecules for Human African Trypanosomiasis - Singh Grewal, Ajmer; Pandita, Deepti; Bhardwaj, Shashikant; Lather, Viney (Current Topics in Medicinal Chemistry, 2016)
Human African trypanosomiasis (HAT, better called as sleeping sickness), caused by two morphologically identicalprotozoan parasite Trypanosoma bruceiis transmitted by the bite of tsetse flies of Glossinagenus, mainly in the rural areas of the sub-Saharan Africa. HAT is one of the neglected tropical diseases and is characterized by sleep disturbance as the main symptom, hence is called as sleeping sickness. As it is epidemic in the poorest population of Africa, there is limited availability of safe and cost-effective tools for controlling the disease. Trypanosoma bruceigambiense causes sleeping sickness in Western and Central Africa, whereas Trypanosoma bruceirhodesiense is the reason for prevalence of sleeping sickness in Eastern and Southern Africa. For the treatment of sleeping sickness, only five drugs have been approved suramin, pentamidine, melarsoprol, eflornithine and nifurtimox. Various small molecules of diverse chemical nature have been synthesized for targeting HAT and many of them are in the clinical trialsincluding fexinidazole (phase I completed) and SCYX-7158 (advanced in phase I). The present work has been planned to review various types of small molecules developed in the last 10 years having potent antitrypanosoma activity likely to be beneficial in sleeping sickness along with different natural anti-HAT agents.
Keywords: Anti-trypanosoma agents